Development and characterization of PHB-HV based 3D scaffolds for a tissue engineering and cell-therapy combinatorial approach for spinal cord Injury regeneration - Samy, S. M. (2013)
Spinal cord injury (SCI) leads to devastating neurological deficits. Several tissue engineering (TE)- based approaches have been investigated for repairing this condition. Poly (3-hydroxybutyrateco- 3-hydroxyvalerate) (PHB-HV) is found to be particularly attractive for TE applications due to its properties, such as biodegradability, biocompatibility, thermoplasticity and piezoelectricity. Hence, this report addresses the development and characterization of PHB-HV-based 3D scaffolds, produced by freeze-drying, aimed to SCI treatment. The obtained scaffolds reveal an anisotropic morphology with a fully interconnected network of pores. In vitro studies demonstrate a lack of cytotoxic effect of PHB-HV scaffolds. Direct contact assays also reveal their ability to support the culture of CNS-derived cells and mesenchymal-like stem cells from different sources. Finally, histocompatibility studies show that PHB-HV scaffolds are well tolerated by the host tissue, and do not negatively impact the left hindlimb locomotor function recovery. Therefore results herein presented suggest that PHB-HV scaffolds may be suitable for SCI treatment.